Extraordinary Response of H-Charged and H-Free Coherent Grain Boundaries in Nickel to Multiaxial Loading - Petr Šesták; Miroslav Černý; Zhiliang Zhang; Jaroslav Pokluda (Crystals, 2020)
The cohesive strength of <semantics> Σ </semantics> 3, <semantics> Σ </semantics> 5, and <semantics> Σ </semantics> 11 grain boundaries (GBs) in clean and hydrogen-segregated fcc nickel was systematically studied as a function of the superimposed transverse biaxial stresses using ab initio methods. The obtained results for H-free GBs revealed a quite different response of the coherent twinning boundary <semantics> Σ </semantics> 3 to the applied transverse stresses in comparison to the other GB types. While the cohesive strength of <semantics> Σ </semantics> 5 and <semantics> Σ </semantics> 11 GBs increased with increasing level of tensile transverse stresses, the strength of <semantics> Σ </semantics> 3 GB remained constant for any applied levels of transverse stresses. In the case of GBs with segregated hydrogen, the cohesive strength of <semantics> Σ </semantics> 3 was distinctly reduced for all levels of transverse stresses, while the strength reduction of <semantics> Σ </semantics> 5 and <semantics> Σ </semantics> 11 GBs was significant only for a nearly isotropic (hydrostatic) triaxial loading. This extraordinary response explains a high susceptibility of <semantics> Σ </semantics> 3 GBs to crack initiation, as recently reported in an experimental study. Moreover, a highly triaxial stress at the fronts of microcracks initiated at <semantics> Σ </semantics> 3 boundaries caused a strength reduction of adjacent high-energy grain boundaries which thus became preferential sites for further crack propagation.